Marmara üniversitesi Teknik Eğitim Fakültesi Matbaa Eğitimi Bölümü mezunların istihdam durumları ve sektördeki durumu - Yücel, Özgür (My University, 2013)
MARMARA ÜNİVERSİTESİ TEKNİK EĞİTİM FAKÜLTESİ MATBAA EĞİTİMİ BÖLÜMÜ MEZUNLARIN İSTİHDAM DURUMLARI VE SEKTÖRDEKİ DURUMU Marmara Üniversitesi Teknik Eğitim Fakültesi Matbaa Eğitimi Bölümü, 1980-1981 öğrenim döneminde ilk mezunlarını vermiş. 2012 yılına kadar geçen sürede bölümden 1617 kişi mezun olmuştur. Matbaa Eğitimi mezunlarının istihdam durumlarının belirlenmesinin yanı sıra, sosyoekonomik profilinin çıkarılması, öğrenim faaliyetleri hakkındaki görüşlerinin ortaya çıkarılması, bu araştırmanın amacını oluşturmaktadır. Araştırmanın evrenini oluşturan 1617 kişiden 1980-2012 yılları arasında mezun olan 213 katılımcıya anket uygulanmıştır. Araştırmada elde edilen veriler doğrultusunda çeşitli çıkarımlar yapılmıştır. Örneğin mezunların %70’inin erkek olduğu ve yıllar ilerledikçe mezunlar arasındaki kadın oranının arttığı anlaşılmaktadır. Mezunların %74,2’sinin İstanbul’da yaşaması ise sektörün bu kentte yoğunlaştığını göstermektedir. Matbaa Eğitimi mezunlarının sadece %21,6’ sı bir kamu kurumunda çalışmakta iken %50,7’ si matbaa sektöründe faaliyet gösteren özel bir firmada görev almaktadır. %21,1’ i ise matbaa alanında istihdam edilmemektedir. Bu veriler aynı zamanda lise düzeyinde meslek eğitimine ve lisans düzeyinde matbaa öğretmenliği eğitimine yönelik yeni bir planlama anlayışının gerekliliğine işaret etmektedir. Anahtar Sözcükler: Mezunlar, anket, istihdam, Matbaa Eğitimi

EMPLOYMENT STATUS OF GRADUATES OF MARMARA UNIVERSITY, FACULTY OF TECHNICAL EDUCATION, DEPARTMENT OF PRINTERY AND THEIR POSITION IN THE SECTOR Marmara University, Faculty of Technical Education, Department of Printery produced its first graduates in 1980-1981 academic years. 1617 people graduated from this department until 2012. The purpose of this research is constructing the social economic profile of the graduates of Department of Printery, bringing out their ideas about the education activities in addition to determining their employment status. Having graduated in 1980-2012 years, 213 participants of 1617 people that constitute system of the research took part in this questionnaire. Certain deductions have been made in accordance with the data obtained from this research. For example, it is understood that the 70 percent of the graduates are male and the rate of female among graduates has been increasing over the years. On the other hand, the fact that the 74,2 percent of the graduates live in Istanbul shows that this sector centers on this city. While the only 21,6 percent of the graduates of Department of Printery work in a public institution, the 50,7 percent of graduates has been employed in a private corporation acting in printery sector. The 21,1 percent of the graduates, on the other hand, are not employed in the printer sector. At the same time, these data point at that a new understanding of planning about professional training on high school level and teaching in printery education on four- year license level is needed. Graduates, questionnaire, employment, Department of Printery
Keywords: İstihdam; Matbaa Eğitimi